2003
DOI: 10.1182/blood-2002-10-3235
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin, a putative mediator of anemia of inflammation, is a type II acute-phase protein

Abstract: Hepcidin is a liver-made peptide proposed to be a central regulator of intestinal iron absorption and iron recycling by macrophages. In animal models, hepcidin is induced by inflammation and iron loading, but its regulation in humans has not been studied. We report that urinary excretion of hepcidin was greatly increased in patients with iron overload, infections, or inflammatory diseases. Hepcidin excretion correlated well with serum ferritin levels, which are regulated by similar pathologic stimuli. In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,093
13
51

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,252 publications
(1,205 citation statements)
references
References 14 publications
48
1,093
13
51
Order By: Relevance
“…Hepcidin expression is increased in obesity 25 and other chronic inflammatory states. 46 Increased circulating hepcidin may reduce both gastrointestinal iron absorption 26 and iron release from the reticuloendothelial system. 47 Although we did not measure hepcidin concentrations, measurements of CRP indicated inflammation was clearly increased with greater adiposity (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin expression is increased in obesity 25 and other chronic inflammatory states. 46 Increased circulating hepcidin may reduce both gastrointestinal iron absorption 26 and iron release from the reticuloendothelial system. 47 Although we did not measure hepcidin concentrations, measurements of CRP indicated inflammation was clearly increased with greater adiposity (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin is downregulated in hypoxia and may explain the increase in iron absorption under hypoxia and the increased iron release from reticuloendothelial cells. Chronic inflammatory models (turpentine injection) in mice result in a pattern similar to anemia of chronic disease [49], and increased urinary excretion of hepcidin is observed in humans with anemia of chronic disease [50]. These data have suggested that hepcidin is the regulator in anemia of chronic disease [51].…”
Section: Physiology Of Ironmentioning
confidence: 93%
“…Kulaksiz et al [7] reported that hepcidin was produced as an intrinsic peptide in the epithelial cells of the tubule and collecting duct in mammalian kidney and may be released luminally into the urine. In a study on 46 patients with chronic renal failure, not yet on dialysis, serum hepcidin correlated with 51Cr-EDTA clearance (r ¼ À0.44; P ¼ 0.005), creatinine clearance, serum creatinine, b-trace protein and cystatin C [5]. However, the authors did not provide biochemical characteristics of the studied population, not even a mean serum creatinine.…”
Section: Introductionmentioning
confidence: 92%